Keys and Clues for Benny - Warner, Gertrude Chandler; Nang Chan Yeema (United States of America Albert Whitman& Company, 2004)
When Benny Alden sees a set of keys that were lost at the library, he follows clues to find the owner.
Keywords: Story Collection